Effect of level of surface-spoiled silage on the nutritive value of corn silage-based rations - Whitlock, L.A.; Wistuba, T.; Siefers, M.K.; Brent, B.E.; Bolsen, K.K.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Twelve ruminally cannulated crossbred steers were used to determine the effects of level of surface-spoiled silages on dry matter (DM) intake and nutrient digestibilities of corn silage-based rations. Irrigated corn was harvested at the 80% milkline stage of maturity and ensiled in 3-ft-deep, pilot-scale, bunker silos and a 9-ft-diameter AgBag®. After 90 days, the bunkers were sealed with a single sheet of polyethylene, and this silage was designated “spoiled”. The silage in the AgBag was designated “normal”. The four rations contained 90% silage and 10% supplement (DM basis). The silages in the rations were: A) 100% normal; B) 75% normal: 25% spoiled; C) 50% normal: 50% spoiled; and D) 25% normal: 75% spoiled. Dry matter intake decreased in a linear manner as the proportion of spoiled silage increased from 0 to 75%. Steers consuming the normal silage ration had higher DM, OM, CP, NDF, and ADF digestibilities than those fed the three rations that contained spoiled silage. The addition of spoiled silage also had negative associative effects on nutrient digestibilities, and the integrity of the forage mat in the rumen was destroyed partially by even the lowest level of surface spoilage.
Keywords: Beef; Corn silage; Surface spoilage; Nutritive value